ROLAND BARTHES' SEMIOTIC ANALYSIS: REPRESENTATION OF MASCULINITY IN EXO'S SCARLETT WHITENING AD (GLOW VERSION) - Annisa Mauliddya; Mirza Azkia Muhammad Adiba (RADJA PUBLIKA, 2025)
The purpose of this study is to analyze the representation of masculinity and brand image building in the Scarlett Whitening x Exo “Glow” advertisement featuring the famous Korean boy band EXO as brand ambassadors. In the analysis, Roland Barthes' semiotic theory is divided into three levels of sign meaning: denotation, connotation, and myth. This study uses a descriptive qualitative approach through semiotic analysis. Data sources were obtained from visual and verbal signs in the advertisement scenes, which were then analyzed to uncover the hidden meanings behind the visual or verbal representations. The research findings reveal that the Scarlett Whitening advertisement presents the concept of masculinity as “soft masculinity,” depicted as flexible masculinity, associating values of gentleness and aesthetic appeal in a man. Through pastel colors, bright hues, soft expressions, stylish and neat clothing, and an ideal physique, the advertisement challenges traditional masculinity stereotypes and creates an image that body care products are relevant and important for men. Scarlett does not merely sell physical products but also promotes a new lifestyle associated with the product, blurring the boundaries between feminine and masculine in self-care